O conceito de Estado Ético e o problema do pensamento utópico na Filosofia Política de Hegel - SIsnando, Alessandro Uchôa (2015)
Starting from the realistic perspective outlined by Hegel's Political philosophy that research clarifies his concept of "Ethical State" by taking into account two crucial moments for its foundation: first, Hegel's criticism of utopian thinking as a shortcoming answer to the problem of State; and second, Hegel's conception as supersession of the essential moments that State itself unfolds throughout history, both in its notional reality (Realitlit) as well as in its actuality (Wirklichkeit). Accordingly, we reconstruct first Hegel's conception of State starting from his interpretation of the Greek organic State in light of Platonic political philosophy; then, we investigate Hegel's critical dialogue with modern political philosophy, in particular the natural law school. Thus, we demonstrate that Hegel's Concept of State was developed as a result of criticizing utopian thinking, considered by Hegel as an obstacle to the development of actual Ethical State, which emerges as the unique locus for achieving substantial freedom out of self-conscious subjectivity. Briefly, our goal is to demonstrate that Hegel's "Ethical State" not only involves the denial of any idealistic conception, but also that the State is a permanent ethical construction characterized by the effective participation of people, expressed by a set of laws mirroring their ethos. Thus, we show that for Hegel there is no a priori ideal model to set up an Ethical State, in so far as its truth results from the historical and social reality of peoples and its establishment is linked to the ability people can have to make its concept effective, viz. to make it coincide its essence with its existence.